A study on Technical Facilities in Municpal Slaughter House and Retail Meat Shops in Bareilly - Sahay, Anupam; Tiwari, Rupasi; Sharma, M C; Roy, Rakesh (Journal of Meat Science, 2011)
The present study was taken up in Bareilly district of Uttar Pradesh to analyze the meat processing and production practices in the municipal slaughter house and retail meat shops. Twenty butchers of large animal slaughterhouse (LAS), ten butchers of small animal slaughterhouse (SAS) and thirty meat retailers were randomly selected for the study. Results of the study revealed that majority of the butchers are with 5 to 15 years of experience, medium work load and without formal training. Various factors for unhygienic meat production include lack of sufficient infrastructure, inefficient and insufficient equipments, poor personal hygiene, poor state of existing buildings of LAS and SAS. Retail meat shops lacked in many important facilities. Majority of meat handlers were unaware of the public health hazards due to lack of training/education. The study reveals that there is an urgent need of creating awareness among butchers and retailers regarding clean and hygienic meat production and associated health hazards.
Keywords: Carcasses; slaughter houses; retail meat shops; hygiene